Os elos entre a questão agrária e a questão racial no contexto de expansão do agronegócio no campo brasileiro - Silva, Samuel Santana (2024)
This paper seeks to analyze, based on economic history, the relationship between the agrarian issue and the racial issue within the dynamics of Agribusiness expansion in the Brazilian countryside. From a historical perspective, the research revisits the colonial processes that gave rise to large estates and racism, highlighting the role of legislation such as the 1850 Land Law. Next, we analyze how the modernization of the agrarian sector has transformed the technical basis and social relations of production while maintaining a highly concentrated agrarian structure in the hands of white landowners. To this end, we use data from the Demographic and Agricultural Censuses. Finally, we discuss the relationship between the agrarian issue and the racial issue in the 21st century, drawing primarily on the 2017 Agricultural Census. This census highlights the increasing concentration of land ownership in Brazil in the 21st century, as small farms lose land while large estates expand their share of occupied territory. It is also the first in the historical series to map rural producers based on their race or color. According to this census, among producers managing establishments with a total area of up to 1 hectare, 57.9% identified as mixed race, 25.5% as white, 13.6% as Black, 8.3% as Indigenous, and 1.8% as Asian. The proportions are starkly different in larger landholdings. In establishments exceeding 500 hectares, the distribution is reversed: 72.2% of owners are white, 23.9% mixed race, 2.5% Black, 0.4% Indigenous, and 0.06% Asian. Thus, we demonstrate that there is indeed a close relationship between racism and Brazilian latifundia, rooted in the country's socio- territorial formation. This relationship has intensified as Agribusiness consolidates and expands further into the countryside, concentrating land ownership increasingly in the hands of white landowners.